Blockchain-Capabilities, Supply Chain Resilience, and Company Performance: : An Empirical Study in Indonesia and Switzerland - Sudrajat, Darjat; Kreie, Andre; Kuncoro, Engkos Achmad; Hakim, Adam Zulyiko (Bina Nusantara University, 2023)
Alignment and agility are essential supply chain capabilities required to maintain and enhance performance, particularly in the current era of disruption. The research aimed to examine the impact of blockchain capabilities on supply chain resilience and company performance using quantitative and cross-sectional survey methods. Logistics service providers (LSP) were selected as the units of analysis, and individuals such as logisticians in Indonesia and Switzerland served as units of observation. Data were collected through an electronic questionnaire (Google Forms) using a quota sampling technique and analyzed using Smart-PLS software. The sample size included 60 respondents, comprising 45 and 15 from Indonesia and Switzerland based on the 10-times rule. The results show that supply chain resilience partially and fully mediated the impact of blockchain capabilities (supply chain alignment and agility) on LSPPerformance. LSP could also enhance performance and resilience by implementing blockchain technology to enhance supply chain alignment and agility. In theoretical terms, the results have implications contributing to dynamic capability theory. In practical applications, the research serves as valuable insights for government authorities and IT consultants when formulating effective plans and strategies to analyze the adoption of blockchain technology among LSP. Additionally, directors and owners of these companies are persuaded that blockchain has the potential to create and enhance supply chain capabilities, as well as increasing competitive advantage.